Cara Efektif Membelajarkan Anak-anak Pinggiran di Pantai Bajo - Sudirman (Universitas Negeri Makassar, 2023)
The motivation to learn among the children of the Bajo Coast (APPB) in Bone Regency is very low. APPB who had attended primary school on average could only last up to grade 5. As a result, there was a massive dropout. They should have continued to study at school, given that compulsory primary education in Indonesia is 6-15 years old. However, they became dropouts whose education was neglected. In fact, there is enough time for them to learn. This phenomenon occurs continuously every year, resulting in the swelling of out-of-school children (ATS). This study aims to find effective ways to ensure that these ATS receive proper education outside the formal school system. The importance of this study is to assist the local government in eradicating ignorance, underdevelopment, and to contribute to reducing the high number of out-of-school children (ATS) in Bone District. A qualitative approach was applied with a case study design. The research subjects were seven APPBs who were selected by purposive sampling, accidental sampling, and snowball sampling. Data were collected through participatory observation and unstructured interviews. The data collected were analyzed qualitatively and descriptively. This study found that (1) an effective way to teach children with disabilities is activity-based learning (PBAN), (2) Bajo Beach children have a kinesthetic learning style who are more eager to learn outside the school system than inside the classroom, and (3) learning would be more meaningful if it was tailored to the characteristics of the children being taught. The conclusion is that children who have very low motivation to learn, if faced with sincerity and make their activities a means of learning, then children can learn well. The results of this study can serve as a reference for the local government in mapping and conducting further studies so that APPB and others in other areas can receive proper education services.